BIOREGENERATIVE LIFE SUPPORT SYSTEMS IN THE SPACE (BLSS): THE EFFECTS OF RADIATION ON PLANTS - Carmen Arena; Veronica De Micco; Amalia Virzo De Santo (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2012)
The growth of plants in Space is a fundamental issue for Space exploration. Plants play an important role in the Bioregenerative Life Support Systems (BLSS) to sustain human permanence in extraterrestrial environments. Under this perspective, plants are basic elements for oxygen and fresh food production as well as air regeneration and psychological support to the crew. The potentiality of plant survival and reproduction in space is limited by the same factors that act on the earth (e.g. light, temperature and relative humidity) and by additional factors such as altered gravity and ionizing radiation. This paper analyzes plant responses to space radiation which is recognized as a powerful mutagen for photosynthetic organisms thus being responsible for morpho-structural, physiological and genetic alterations. Until now, many studies have evidenced how the response to ionizing radiation is influenced by several factors associated both to plant characteristics (e.g. cultivar, species, developmental stage, tissue structure) and/or radiation features (e.g. dose, quality and exposure time). The photosynthetic machinery is particularly sensitive to ionizing radiation. The severity of the damages induced by ionizing radiation on plant cell and tissues may depend on the capability of plants to adopt protection mechanisms and/or repair strategies. In this paper a selection of results from studies on the effect of ionizing radiations on plants at anatomical and eco-physiological level is reported and some aspects related to radioresistance are explored.